Coherence of Bangui Magnetic Anomaly with Topographic and Gravity Contrasts across Central African Republic - (:unkn) unknown (My University, 2023)
The interactions between the geophysical processes and geodynamics of the lithosphere play a crucial role in the geologic structure of the Earth's crust. The Bangui magnetic anomaly is a notable feature in the lithospheric structure of the Central African Republic (CAR) resulting from a complex tectonic evolution. This study reports on the coherence in the geophysical data and magnetic anomaly field analysed from a series of maps. The data used here include raster grids on free-air altimetric gravity, magnetic EMAG2 maps, geoid EGM2008 model and topographic SRTM/ETOPO1 relief. The data were processed to analyse the correspondence between the geophysical and geologic setting in the CAR region. Histogram equalization of the topographic grids was implemented by partition of the raster grids into equal-area patches of data ranged by the segments with relative highs and lows of the relief. The original data were compared with the equalized, normalized and quadratic models. The scripts used for cartographic data processing are presented and commented. The consistency and equalization of topography, gravity and geoid data were based using GMT modules 'grdfft' and 'grdhisteq' modules. Using GMT scripts for mapping the geophysical and gravity data over CAR shows an advanced approach to multi-source data visualization to reveal the relationships in the geophysical and topographic processes in central Africa. The results highlighted the correlation between the distribution of rocks with high magnetism in the central part of the Bangui anomaly, and distribution of granites, greenstone belts, and metamorphosed basalts as rock exposure. The correspondence between the negative Bouguer anomaly (<−80 mGal), low geoid values (<−12 m) and the extent of the magnetic anomaly with extreme negative values ranging from −1000 to −200 nT is identified. The integration of the multi-source data provides new insights into the analysis of crustal thicknesses a
Keywords: African Research